2021
DOI: 10.3390/jtaer16050102
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Traits and Intention to Use E-Commerce among Rural Micro-Entrepreneurs in Malaysia

Abstract: This study was set out to chiefly examine the influence of psychological traits—need of achievement (“N of Ach”) and risk-taking propensity (RTP)—on perceived usefulness (PUF) and perceived ease of use (PercEU), as well as their effects on the intention to use e-commerce among rural micro-entrepreneurs. This study exploited the psychological traits theories and the technology acceptance model (TAM) by utilizing samples represented by rural micro-entrepreneurs. The results of the study found that the N of Ach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
(78 reference statements)
1
4
0
1
Order By: Relevance
“…other variables such as ATU the system, BI, and U were observed to have been used by some studies while others do not use them. Type of Technology TAM Model [60] Online Government Credit Program Extended TAM with Model 4 As [61] E-Commerce TAM and entrepreneurial traits theory [55] Social Media Marketing Extended TAM with added variable (education) [52] Financial Technology Application Extended TAM with added variable (Trust) [56] Financial technology Extended TAM [5], [6] Digital Payment System Extended TAM with added variable (Trust) [5] Financial Technology Extended TAM [43] Digital Media Theory of Pace of technological innovation and TAM [37] Accounting Information System TAM [54], [62] Social Media Marketing Extended TAM [44] Internet Banking Extended TAM [9] Knowledge Management based web application…”
Section: Discussion Rq 1: What Are the Most Relevant Factors Influencing Smes In Adopting Technology Based On Tam?mentioning
confidence: 99%
“…other variables such as ATU the system, BI, and U were observed to have been used by some studies while others do not use them. Type of Technology TAM Model [60] Online Government Credit Program Extended TAM with Model 4 As [61] E-Commerce TAM and entrepreneurial traits theory [55] Social Media Marketing Extended TAM with added variable (education) [52] Financial Technology Application Extended TAM with added variable (Trust) [56] Financial technology Extended TAM [5], [6] Digital Payment System Extended TAM with added variable (Trust) [5] Financial Technology Extended TAM [43] Digital Media Theory of Pace of technological innovation and TAM [37] Accounting Information System TAM [54], [62] Social Media Marketing Extended TAM [44] Internet Banking Extended TAM [9] Knowledge Management based web application…”
Section: Discussion Rq 1: What Are the Most Relevant Factors Influencing Smes In Adopting Technology Based On Tam?mentioning
confidence: 99%
“…Also considering indirect effects only, Wang et al [42] found that the risk-taking propensity trait was related to attitudes toward online shopping, which, in turn, were related to the intention to shop online. Also considering the indirect effects of risk-taking propensity, along with the need for achievement of entrepreneurs, Yusoff et al [60] found that both traits were positively related to perceived usefulness and perceived ease of use, which were related to the intention to participate in e-commerce (survey, n = 302, Malaysia).…”
Section: Further Personality Traits and Their Influence On Channel Choicementioning
confidence: 99%
“…• Intuitive (Barkhi and Wallace [44] through ease of use, attitude) • Need of achievement (Yusoff et al [60] through usefulness, ease of use) • Neuroticism/-anxiety (neg., Bosnjak et al [38]; neg., Lixăndroiu et al [47]; McElroy et al [46]; neg., San-Martin et al [49] through gaming and online shopping self-efficacy; neg., Zhu et al [53]) • Openness (Bosnjak et al [38]; Wang et al [42] through attitude) • Perceptive (Barkhi and Wallace [44] through peer influence, attitude) • Playfulness (Wu and Ke [27]) • Risk-taking (Wang et al [42] through attitude; Yusoff et al [60] through usefulness, ease of use) • Self-esteem (Breazeale and Lueg [52])…”
Section: Summary Of the Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…La utilidad percibida (up) hace referencia a la medida en la que un individuo intuye que cierto tipo de tecnología resultará conveniente para sí mismo (Laith & Abdullah, 2021). Esto se define, dentro del e-commerce, como el grado de beneficio que un consumidor piensa que recibirá al realizar transacciones online (Capece et al, 2013;Yusoff et al, 2021).…”
Section: Utilidad Percibidaunclassified